SOCIAL ANXIETY IN SOCIAL MEDIA USERS: UNDERSTANDING THE ROLE OF SELF-ESTEEM AND DEMOGRAPHIC FACTORS - Rahardjo, Wahyu; Mardianti, Mardianti (Mediakom : Jurnal Ilmu Komunikasi, 2023)
Social anxiety can occur online when individuals use social media. Several factors that are thought to influence social anxiety using social media are self-esteem and demographic factors such as age, gender, and duration of social media use. The aim of this research is to measure empirically whether these variables are determinants of social anxiety using social media. The participants of this research are 164 active social media users who live in the Jakarta Greater Area. The social anxiety scale for social media users and the self-esteem scale are used as research instruments. The data analysis technique used is regression to measure the role of self-esteem on social anxiety using social media. Meanwhile, correlation tests and difference tests were carried out to determine the position of demographic variables in relation to social anxiety using social media. The research results show that age has a significant negative correlation, while the duration of social media use has a significant positive correlation with social anxiety using social media. On the other hand, self-esteem is proven to have an influence on all aspects of social anxiety using social media. The strongest effect appears on interaction anxiety, and the weakest effect appears on privacy content anxiety. The research results also showed that female participants had higher social anxiety using social media than male participants.